Mitigative effects of a topically-applied combination of cimifugin and vinpocetine on a murine psoriasis-like model - Abbas, Alaa Hamza; M. Hassan, Zaid; A. Albarki, Mohammed; A. Zigam, Qassim; Ridha-Salman, Hayder; A. M. Abbas, Hasanain; Ahmed AbdulAemah, Maytham; J. Abbas, Weaam; K. Raheem, Abdulla; Hemid Al-Athari, Ali Jihad; et al. (Pharmakeftiki, 2025)
The chromones found in the dried roots of Saposhnikovia divaricata include cimifugin; in fact, Saposhnikovia divaricata is a main source of cimifugin. Vinpocetine is a synthetic version of vincamine derived from periwinkle; it is characterized by potent anti-inflammatory properties that allow it to reduce immune cell infiltration and suppress the release of pro-inflammatory cytokines. The objective of this study was to investigate the potential influence of a topically-applied combination of cimifugin and vinpocetine gels on a model of a psoriasis-like inflammatory skin reaction. To this end, we divided 48 albino BALB/c mice into six groups. All groups except for the negative control group received imiquimod topically (daily, for 7 days) for the induction of psoriasis-like skin lesions. A group received imiquimod (5%) only (positive control), while four other groups were also treated with a clobetasol (0.05%) cream, a cimifugin (3%) gel, a vinpocetine (3%) gel, or a combination of cimifugin (3%) and vinpocetine (3%) gels, once daily, for 7 days; the aforementioned treatments were first applied 7 days after the pharmacological induction of the lesions. Our findings revealed that the topically-applied combination of cimifugin- and vinpocetine-containing gels had an important anti-psoriatic effect, as seen by the diminishing of the skin levels of tumour necrosis factor-alpha, interleukin-17, and interleukin-23, thereby improving the imiquimod-induced histological changes in mice. We conclude that a topically-applied combination of cimifugin and vinpocetine can exert substantial anti-psoriatic activity.